Cobalt Tungsten Oxide Thin Films Prepared by RF‐Sputter for Photosensor. Issue 11 (8th March 2017) - Lan, Kai‐Wei; Hong, Ying‐Jhan; Chang, Pin; Yew, Tri‐Rung
Abstract : This study reports the synthesis and characterization of nonstoichiometric nanocrystalline Co2.59 W0.41 O4 thin film by the radio frequency (RF)‐sputter technique suitable for photosensor applications. The photoconductive characteristics of Co2.59 W0.41 O4 thin film are investigated by fabricating a sandwich‐structure device of p + Si/Co2.59 W0.41 O4 thin film/indium tin oxide with Schottky barriers. The device characteristics including responsivity, light intensity response, and time response are studied. It is found that Co2.59 W0.41 O4 thin film exhibits good absorption (absorption coefficient ≈10 4 cm −1 in visible light spectrum), relatively high responsivity ( R res = 5.427 A W −1 ), and fast photoresponse time including rise time ( t r ) = 81.04 ms and fall time ( t f ) = 80.67 ms. Hence, the Co2.59 W0.41 O4 thin film is favorable for potential photosensor applications. Abstract : The composition of oxide semiconductors can be tailored to enhance their absorption and induce photoconductivity. Nevertheless, there is still no report of photosensors fabricated from the mixture of Co3 O4 and WO3 to form cobalt tungsten oxide that can provide photoconducting properties yet. This study reports successful formation of nonstoichiometric nanocrystalline Co2.59 W0.41 O4 thin film by radio frequency (RF)‐sputter and postannealing at 300 °C.